Divining Nature: Aesthetics of Enchantment in Enlightenment France - Cuillé, Tili Boon (Stanford, CA Stanford University Press, 2021)
"Divining Nature traces the philosophical, aesthetic, and affective responses to the "spectacle of nature" across the arts and sciences in eighteenth-century France to uncover the preservation and proliferation of wonder in the age of reason"
Introduction : the spectacle of nature -- The marvels of nature in Buffon and Rameau -- The philosophy of nature in Diderot and Rousseau -- The harmony of nature in Paul et Virginie -- The poetics of nature in Ossian and Staël -- Epilogue : a theater of enchantment.
Includes bibliographical references and index.
Keywords: Rameau, Jean-Philippe -- 1683-1764; Diderot, Denis -- 1713-1784; Rameau, Jean-Philippe -- 1683-1764; 18th Century (1701-1800); Enlightenment; Science; Opera; Esthetics; France